Synthesis of Functionalized Pyrazolo[1,5-a]pyridines: [3+2] Cycloaddition of N-Aminopyridines and α,β-Unsaturated Carbonyl Compounds/Alkenes at Room Temperature - Ravi, Chitrakar; Samanta, Supravat; Mohan, Darapaneni Chandra; Reddy, N. Naresh Kumar; Adimurthy, Subbarayappa (Synthesis, 2017)
The synthesis of functionalized pyrazolo[1,5-a]pyridines through oxidative [3+2] cycloaddition of N-aminopyridines with α,β-unsaturated carbonyl compounds or electron-withdrawing olefins is described. The reactions proceed in N-methylpyrrolidone as the solvent under metal-free conditions at room temperature.
Keywords: N-methylpyrrolidone; chalcones; metal-free; drug intermediates; [3+2] cycloaddition